Walter Benjamin and the aesthetics of film - Mourenza, Daniel (Amsterdam University Press, 2020)
Walter Benjamin is today regarded as one of the leading thinkers of the twentieth century. Often captured in pensive pose, his image is now that of a serious intellectual. But Benjamin was also a fan of the comedies of Adolphe Menjou, Mickey Mouse, and Charlie Chaplin. As an antidote to repressive civilization, he developed, through these figures, a theory of laughter. Walter Benjamin and the Aesthetics of Film is the first monograph to thoroughly analyse Benjamin's film writings, contextualizing them within his oeuvre whilst also paying attention to the various films, actors, and directors that sparked his interest. The book situates all these writings with Benjamin's 'anthropological materialism', a concept that analyses the transformations of the human sensorium through technology. Through the term 'innervation', Benjamin thought of film spectatorship as an empowering reception that, through a rush of energy, would form a collective body within the audience, interpenetrating a liberated technology into the distracted spectators. Benjamin's writings on Soviet film and German cinema, Charlie Chaplin, and Mickey Mouse are analysed in relation to this posthuman constellation that Benjamin had started to dream of in the early twenties, long before he started to theorize about films.